Paradoks Perlindungan Kekayaan Intelektual dalam Pencetakan 3D Hasil Desain Artificial Intelligence (AI): Indonesia vs. Vietnam - Hari Sutra Disemadi; Agustianto Agustianto (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
The utilization of advanced technologies in the context of digital transformation plays a crucial role in economic progress and growth. However, the use of cutting-edge technologies such as AI and 3D printing must be supported by an adequate legal framework to prevent violations of intellectual property protection principles and avoid harming intellectual property holders. This study aims to explore the issues that may arise from the use of AI and 3D printing technologies. Using a normative legal research method with a comparative approach, this study analyzes the paradox of protection created by these issues, while highlighting the problems found in the legal norms of relevant legal frameworks, such as patent and industrial design regimes. The analysis reveals limitations in the application of the exhaustion doctrine, which could provide balanced protection for the use of these two advanced technologies. Based on these findings, the study offers recommendations for strategic legal development that could be applied by Indonesia and Vietnam, as two ASEAN countries with significant potential in the era of digital transformation.